Case studies of online control of energy storage system - Wang, Jingfeng (2014)
In the Laboratory for Clean Energy Research (LaCER), a 5kVA bi-directional Lithium-ion energy storage battery system has been installed with the associated battery management software and a DC to three-phase 0.4kV inverter. The state of charge, abbreviated as “SOC”, is the essential battery parameter monitored in system to indicate the remained capacity of the battery pack. Especially in case of BMS (Battery Management System) implementation of balancing circuits, SOC will indicate when to charge or discharge the batteries connected in series. Therefore, an effective and accurate SOC estimating method would be very necessary to be proposed and developed.